The Artistry of Fairy Tale-Epic (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In the “O‘qish kitobi” (Reading Book) textbooks, prose literary tales are called "literary fairy tales", lyric-epic literary tales are called "poetic literary tales", fairy tales are epics; folk tales should be given in the form of "tale" or "Uzbek folk tale" or "Arab folk tale". Giving rules to genres such as stories, poems, legends, and narratives, based on the principle from simple to complex, increases the level of children's perception of artistic works.